SISTEM PENDIDIKAN DAN PELATIHAN DALAM UPAYA PENINGKATAN KINERJA SUMBER DAYA MANUSIA DI PT TELEKOMUNIKASI INDONESIA, TBK. JAKARTA SELATAN - Siti Annisa Wahdiniawati; M. Syamsul Ma`arif; Sukiswo Dirjosuparto (Pusbindiklat - LIPI, 2014)
According to the Indonesian Government Regulation No. 101 of 2000, the education and training system covers the process of identifying needs, planning, implementation and evaluation of education and training. Edu- cation and training is aimed to prepare employees to meet the requirements and needs of the organization, includ- ing procurement of leaders and staff cadres. The purposes of this study are to identify the factors of education and training as well as performance indicators and to analyze the factors that are the most dominant influences on the performance of employees at PT Telekomunikasi Indonesia, Tbk South Jakarta. Human resources referred to in this research are permanent employees of PT Telkom, who take part in education and training. The research was conducted by questionnaire to 100 employees in the unit of Customer Service (CS) at PT Telekomunikasi Indonesia, Tbk South Jakarta. The sampling method was conducted by Judgement Sampling. The method of hypothesis testing uses the Structural Equation Model (SEM) with Smart PLS Software 2.0.